(3HMGQ GdCfhGQs - (3eMeO HGbQ Hf eMeO Jbj Hf ebUhO Ydj GdCUagGfj, J (B1111 (3g` s
(3ChdgG (B:s
(3HGH bVGjGg UdhGJ Gddg Ydjg hbO ChQOfG cKjQkG ef bVGjGg s
(3BNQgG (B:s
(3GSJYedg ai JMUjd GdOGQ GdaGfjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B91s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(1425) s
Keywords: (3abg GdePGgH GdCNQis